Development of immunoglobulin variable heavy chain gene consensus probes with conjugated 3′ minor groove binder groups for monitoring minimal residual disease in childhood acute lymphoblastic leukaemia. Issue 12 (25th November 2003) - Uchiyama, M; Maesawa, C; Yashima, A; Itabashi, T; Satoh, T; Tarusawa, M; Endo, M; Takahashi, Y; Sasaki, S; Tsuchiya, S; Ishida, Y; Masuda, T
Abstract : Aims: To develop immunoglobulin heavy chain variable (VH) gene probes that are shorter and more flexible in position for monitoring minimal residual disease (MRD) in childhood leukaemia (ALL), using minor groove binder (MGB) technology. Methods: All VH germline sequences registered in the database were aligned and the consensus regions were determined. The reliability of the MGB probes was compared with non-MGB probes in all 24 cases of ALL. Results: Ten MGB probes (16 to 18 mers) were designed that enabled all the germline sequences on the database to be analysed, whereas the conventional non-MGB probes (21 to 27 mers) did not allow the analysis of four of the VH1 and five of the VH3 germline sequences. The sequencing results in five of the 24 cases of ALL were not matched to the non-MGB probes. Conclusions: MGB technology allows shorter probes to be designed, enabling MRD to be detected in childhood ALL. This would provide a considerable reduction in cost for a large MRD study.